Measuring customer perception towards road transport department branches based on content analysis / Wan Aqmal Azhar W Abd Aziz, S.Sarifah Radiah Shariff and Wan Mazlina Wan Mohamed - Abd Aziz, Wan Aqmal Azhar W; Radiah Shariff, S.Sarifah; Wan Mohamed, Wan Mazlina (Universiti Teknologi MARA, 2022)
Customer perception is an important element for all service providers including government office. The road transport enforcer, Road Transport Department (RTD) Malaysia always ensures that the customers are satisfied with their services especially at their service counters throughout the country. Customer perception is shaped by multiple variables including direct and indirect interaction offered by government office like RTD. In this study, customers' perception towards RTD Perak state is explored. This includes all six branches within Perak state which are UTC Ipoh branch, Taiping Branch, Manjung Branch, Tapah Branch and Teluk Intan Branch, based on google maps review star rating. Details analysis on the comments left by the customers is done using content analysis and correlation analysis. Result shows the positive impact for the RTD especially and all public servant agencies generally